Gestión del conocimiento en una organización intensiva en conocimiento: el caso de un Centro de Investigación de Excelencia en Colombia (2012)
This article is the result of a research project denominated “Towards building a scorecard for knowledge management centers of excellence: a Colombian case study”, developed by the research group Humanism and Management, Universidad del Valle. It presents an approach to a knowledge-management model for a knowledge-intensive organization (KIO) in Colombia. The study is descriptive and inductive, with qualitative research techniques, and primary and secondary information sources. The main objective is to identify and characterize knowledge management in a KIO in Colombia. For the specific case, a Research Center of Excellence (RCE) in the country was chosen, due to its research orientation.